If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 + (x + -7) = 90 Reorder the terms: 45 + (-7 + x) = 90 Remove parenthesis around (-7 + x) 45 + -7 + x = 90 Combine like terms: 45 + -7 = 38 38 + x = 90 Solving 38 + x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + x = 90 + -38 Combine like terms: 38 + -38 = 0 0 + x = 90 + -38 x = 90 + -38 Combine like terms: 90 + -38 = 52 x = 52 Simplifying x = 52
| 6x=5000 | | a=25(.15)10 | | n/3-8=12 | | 2+-8=-24 | | 4(3x+11)=37(16+4x) | | 4(3x+11)=2.9(16+4x) | | 35-6u=u | | 4(3x+11)=2.6(16+4x) | | -f(x)=x^2+5x-2 | | 4(3x+11)=2.7(16+4x) | | 4(3x+11)=0(16+4x) | | 4(3x+11)=2.5(16+4x) | | 9-7v-1.1-8v= | | y=-x^2+5x+14 | | 2m+8-7m=23 | | .0833(156x-17)=5(18+12x) | | 9a-20= | | Cos^2x-5sinx-5=0 | | f(x)=-163+200x | | 12-w=52 | | 10x-14.30=26.00 | | 3(2m+4)=6m+12 | | H+28.80=86.40 | | x(.97)=275 | | H(x)=6x+2 | | H+1=28.80 | | (-2x^3+x)+(3x-6)= | | 3y+6=5y+2 | | 2-m/2 | | 275=x-(3/100) | | (45x-15)/5 | | 3x^2-14x+18=3 |